Design, development and operation of uavs for remote sensing - Ewing, Mark S. (Kansas State University, 2013)
The Flight Research Lab, in partnership with the Center for Remote Sensing of Ice Sheets (CReSIS), has developed an ice-penetrating radar system on a 1100 lb gross takeoff weight/100 lb payload UAV. Based on radar miniaturization, a UAV with a 75 lb gross takeoff weight/20 lb payload has recently been designed and is currently in flight test. Both systems were designed based on the radar system requirements. For the 1100 lb Meridian, the radar mass and flight range dictated the size of the aircraft, and resulted in a unique spot in design space not available from existing vehicles. For the 75 lb YAK/G1X, an available “kit” aircraft nearly fit the bill, but a larger wing was needed for the radar; so a longer wing was designed for the stock fuselage. CReSIS and KU Composites Lab teams have fielded numerous radar systems for crewed aircraft including the DC-8, P-3 and Twin Otter. These radar have imaged bedrock beneath as much as 3.5 km of ice in Antarctica, giving glaciologists never-before seen glimpses of the topography of the continent. Now, radar have been designed for UAVs with the goal of reducing the danger of human flight over glaciers. [Last year a Twin Otter crew was lost in Antarctica in a quickly-moving storm.] The Flight Research Lab has developed a design/build/test process to provide semi-autonomous, remote sensing UAV platforms to meet unique sensing needs. Full-time staff is augmented by talented undergrads and graduate students who work on the team as they learn relevant analysis, design, fabrication and test skills. Flight test partners include private contractors, Kansas businesses and the KSU Aviation Technology Department. Some of the unique design features to be discussed include: • Carbon fiber and glass fiber structures augmented with both aluminum and wood substructure • Customized avionics (autopilot, navigation, communications and power distribution) • Quasi-real-time simulation processes for nonlinear aircraft dynamics identification and control system design, which enable smaller UAVs which are more agile (think able to avoid others) Some of the evolving technologies to be discussed include “flight director” systems coupling autopilot, navigation and situational awareness systems for see/sense & avoid capability, including cognitive architectures for on-board decision-making.
Keywords: Unmanned air vehicles; Radar; Antarctica; Remote sensing; Ice sheets